An overview of program Pembudayaan Keusahawanan Politeknik Kuching Sarawak (Multiskills Training Centre) / Christina Muti Alexander - Alexander, Christina Muti (University Technology MARA Sarawak, 2015)
Multiskills Training Centre is a new company which to provide an effective training to people especially to the Bumiputera in order to gain the development of society and economy into the business. This company owned by Tn. Haji Abang Yusuf bin Abang Spawi. Thus, in this chapter explain about the background, objective, mission and so forth.